Ecological and Evolutionary Benefits of Temperate Phage: What Does or Doesn't Kill You Makes You Stronger - Harrison, Ellie; Brockhurst, Michael A. (BioEssays, 2017)
Infection by a temperate phage can lead to death of the bacterial cell, but sometimes these phages integrate into the bacterial chromosome, offering the potential for a more long‐lasting relationship to be established. Here we define three major ecological and evolutionary benefits of temperate phage for bacteria: as agents of horizontal gene transfer (HGT), as sources of genetic variation for evolutionary innovation, and as weapons of bacterial competition. We suggest that a coevolutionary perspective is required to understand the roles of temperate phages in bacterial populations. The dual personality of temperate phages – as infectious lytic phages or prophages integrated within the bacterial genome – creates a complex interaction with bacterial hosts. Although potentially lethal, prophages confer a multitude of benefits for the host, suggesting the potential for both conflict and collaboration which must be viewed from a coevolutionary perspective that considers both host and phage fitness interests.